Development of a Web Sharing System of Human Body Data Using Lightweight JavaEE (Journal of Fiber Bioengineering and Informatics, 2008)
This paper presents a method based on lightweight JavaEE for developing the web sharingsystem of human body data. This method is based on the feature that the body data is collected bydifferent 3D laser body scanners from different places and the design ideal of this method is directedby UP (The Unified Software Development Process). Some open source tools (such as struts,spring and hibernate) has been introduced in this project for building the project efficiently. In WebSharing System of Human Body Data, struts framework has been used for building the presentationlayer, spring for business and logic layer, hibernate for data persistent layer. For using different datapersistent strategy flexibility, the MODEL (data access object) layer has been abstracted in this method.This method not only meets the requirement of OCP(Open-Closed Principle) in computer softwaredevelopment, and does the best way to avoid the problems of rigidity, fragility, immobility andviscosity, but also has the features of extensibility, flexibility and pluggability in software design.